Serum anti-tetanus and measles antibody titres in Ugandan children aged 4 months to 6 years: implications for vaccine programme - Warrener, Lenesha; Bwogi, Josephine; Andrews, Nick; Samuel, Dhanraj; Kabaliisa, Theopista; Bukenya, Henry; Brown, Kevin; Roper, Martha H.; Featherstone, David A.; Brown, David (Epidemiology and Infection, 2018)
To study the antibody response to tetanus toxoid and measles by age following vaccination in children aged 4 months to 6 years in Entebbe, Uganda. Serum samples were obtained from 113 children aged 4–15 months, at the Mother-Child Health Clinic (MCHC), Entebbe Hospital and from 203 of the 206 children aged between 12 and 75 months recruited through the Outpatients Department (OPD). Antibodies to measles were quantified by plaque reduction neutralisation test (PRNT) and with Siemens IgG EIA. VaccZyme IgG EIA was used to quantify anti-tetanus antibodies. Sera from 96 of 113 (85.0%) children attending the MCHC contained Measles PRNT titres below the protective level (120 mIU/ml). Sera from 24 of 203 (11.8%) children attending the OPD contained PRNT titres <120 mIU/ml. There was no detectable decline in anti-measles antibody concentrations between 1 and 6 years. The anti-tetanus antibody titres in all 113 children attending MCHC and in 189 of 203 (93.1%) children attending the OPD were >0.15 IU/ml by EIA, a level considered protective. The overall concentration of anti-tetanus antibody was sixfold higher in children under 12 months compared with the older children, with geometric mean concentrations of 3.15 IU/ml and 0.49 IU/ml, respectively. For each doubling in age between 4 and 64 months, the anti-tetanus antibody concentration declined by 50%. As time since the administration of the third DTP vaccination doubled, anti-tetanus antibody concentration declined by 39%. The low measles antibody prevalence in the children presenting at the MCHC is consistent with the current measles epidemiology in Uganda, where a significant number of measles cases occur in children under 1 year of age and earlier vaccination may be indicated. The consistent fall in antitetanus antibody titre over time following vaccination supports the need for further vaccine boosters at age 4–5 years as recommended by the WHO.
Keywords: Antibody persistence; Measles vaccination; Tetanus toxoid